RIGHTS OF FIXED-TERM EMPLOYMENT CONTRACT WORKERS IN A DISMISSAL (STUDY OF SUPREME COURT DECISION NUMBER 175 K/PDT.SUS-PHI/2020) - Vanessa Wijaya; Gunardi Lie (Fakultas Hukum Universitas Tarumanagara, 2022)
Indonesia is listed as one of the most densely populated countries in the world. Hard competition in the world of work, low education levels and high population growth rates supported by minimal employment opportunities which are not followed by very rapid population growth rates are the background of the gap between human resources that meet company qualifications and job seekers. Trying their luck as a laborer/worker in the PKWT system is a step often taken by job seekers so as not to be unemployed and to make ends meet. As was the case with 2 (two) marketing workers at PT Sinarmas Multifinance Yogyakarta Branch, who worked with PKWT status. Declared that they did not reach their target, both of them had to swallow the bitter pill that they were 'kicked' from the company without getting the rights that both of them should have. However, as far as the research conducted by the author, the author found several irregularities that escaped the attention and consideration of the Panel of Judges. In this study, the authors will re-analyze the Yogyakarta District Court Decision No. 35/Pdt.Sus-PHI/2019/PN.Yyk. as a decision at the first level, Supreme Court Decision No. 175 K/Pdt.Sus-PHI/2020 as a decision at the cassation level, by applying the relevant laws and regulations as well as decisions from several similar cases.